Pyridoxine requirement of broilers on fed guinea com-palm kernel meal based diet - R. A., Oloyo (Universiti Putra Malaysia Press, 2001)
A trial was conducted to establish pyridoxine requirement of broilers fed on practical ration, in which 8 duplicate groups of25 commercial broiler chicks were fed guinea corn-palm kernel meal based diet supplemented with graded levels of pyridoxine (4.5, 5.0, 5.5, 6.0, 7.0, 7.5 and 8.0 mg/kg feed) from day-one to 42 days. Data on feed utilisation, nutrient retention and carcass characteristics showed that 6.0mg pyridoxine/kg feed is the minimum requirement whereas 5.5mg/kg feed was required for prevention of mortality and maintenance of normal haemoglobin concentration, packed cell volume (PCV) and aspartate aminotransferase activities in serum and liver.